Vietovardžių apibendrintų skiemens modelių statistinė analizė - Kliukienė, Regina (Lietuvių kalba, 2007)
The article deals with the syllable structure of toponyms and with the general regularities of the syllable phonotactics. The experiment has been carried out using the original software SKIEMUO. PAS. (the programming language Turbo Pascal. 7), developed by A. Girdenis. The results obtained can be summarised as follows: toponyms account for 22 generalised structures; the CV type syllable structure is the most productive; vowel syllables prevail; open covered asymmetrical syllables are more common than others; polynomial consonant clusters in toponyms are rare; toponyms are polysyllabic words; their average length is 3.128 syllables.